A Natural History of Coastal Sage Scrub in Southern California: Regional Floristic Patterns and Relations to Physical Geography, How It Changes Over Time, And How Well Reserves Represent Its Biodiversity - Taylor, Robert S. (Geography, 2004)
This dissertation is a study of coastal sage scrub in coastal southern California. Research questions concern patterns of species distribution, composition of major species associations, environmental correlates with species distributions and changes in vegetation composition and structure over time. Implications for conservation biology and resource management of this scarce and rapidly vanishing resource are discussed. A digital, spatial database of historic composition in southern Californian shrublands is constructed by examination of historic documents from an extensive vegetation survey conducted between 1929 and 1934 by the U. S. Forest Service (the Vegetation Type Map survey). This data is combined in a GIS with climate, fire history, environmental and modern land use data. A subset of 78 plots representing a wide range of site histories and environmental conditions was resampled in 2000 to assess vegetation change over 70 years. In Chapter 1, I examine general organizing principles of shrubland plant communities in southern California, with a focus on coastal sage scrub. Classification and ordination methods are used to describe general patterns of species abundance and distribution in chaparral and coastal sage scrub vegetation types. In a more detailed analysis of species associations and floristic patterns in the coastal sage scrub plots, different types of coastal sage scrub are described. Physical environmental effects on the distribution of dominant species are measured. Results are compared to other published descriptions of coastal sage scrub. In Chapter 2, changes in vegetation composition and structure are described. I compare changes in vegetation composition noted between 1930 and 2000 to environmental factors, patterns of land use, disturbance, and stand fragmentation caused by urbanization. Air photo interpretation is used to make broader conclusions about observed changes. Findings are compared to other studies conducted in similar vegetation types. In Chapter 3, I compare distributions of the main species associations derived in Chapter 1 with modern land use and ownership data to estimate loss of various coastal sage scrub types. I conduct a gap analysis to assess representation of coastal sage scrub’s historic diversity in the Natural Communities Conservation Program (NCCP) reserve system.
Keywords: coastal sage scrub; VTM; Wieslander